2001
DOI: 10.5038/2375-0901.3.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Garden State Parkway Alternate Bus Routing Field Operational Test

Abstract: This study evaluates the effectiveness of the New Jersey Garden State Parkway (GSP) Alternate Bus Routing (ABR) system, an Advanced Public Transportation System (APTS). The GSP ABR Field Operational Test (FOT), which was conducted on a small portion of the parkway, was mainly concerned with real-time routing of New Jersey Transit (NJT) IntroductionOne of the most efficient ways to understand and assess the effectiveness of Intelligent Transportation Systems (ITS) in improving the existing transportation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A summary of diversion messages compiled during the testing period showed that no diversion message, except one on December 11, 1997, lasted more than 15 minutes (Ozbay et al 1998). The real length of the diversion message is a multiple of 4 minutes because the system issues new diversion messages at this rate.…”
Section: Bus Travel-time Reduction Test (Sw-01)mentioning
confidence: 99%
“…A summary of diversion messages compiled during the testing period showed that no diversion message, except one on December 11, 1997, lasted more than 15 minutes (Ozbay et al 1998). The real length of the diversion message is a multiple of 4 minutes because the system issues new diversion messages at this rate.…”
Section: Bus Travel-time Reduction Test (Sw-01)mentioning
confidence: 99%